Investigating the Effects of Language-Switching Frequency on Attentional and Executive Functioning in Proficient Bilinguals - Barbu, Cristina-Anca; Gillet, Sophie; Poncelet, Martine (Frontiers in Psychology, 2020)
Recent studies have proposed that the executive advantages associated with bilingualism may stem from language-switching frequency rather than from bilingualism per se (see for example, Prior & Gollan, 2011). Barbu, Gillet, Orban and Poncelet (2018) showed that high-frequency language switchers outperformed low-frequency switchers on a mental flexibility task but not on alertness or response inhibition tasks. The aim of the present study was to replicate these results as well as to compare proficient high and low-frequency bilingual language switchers to a control group of monolingual participants. Two groups of proficient bilingual adults (30 high-frequency language switchers and 21 low-frequency language switchers) and a group of 28 monolinguals participated in the study. The results showed superior mental flexibility skills in high-frequency language switchers compared to low-frequency switchers and monolinguals; furthermore, the two latter groups showed no difference in mental flexibility skills. These results provide novel support for the hypothesis that the so-called bilingual advantage is, in fact, a result of language-switching habits.